2016
DOI: 10.1111/jfbc.12271
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity andα-Amylase Inhibitory Effect of Polyphenolic-Rich Extract fromOriganum GlandulosumDesf

Abstract: The polyphenolic-rich extract of Tunisian Origanum glandulosum Desf. was investigated for its phenolic composition, antioxidant activity and potential to contribute to the dietary management of type II diabetes. By mean of an ultraperformance liquid chromatography-electrospray ionization-mass spectrometry (UPLC-PDA-ESI-MS) 16 phenolics were characterized. The major detected compounds are caffeic acid, luteloin glucoside, xanthomicrol and carvacrol. The polyphenolic-rich extract presented a notable antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Both the activity of α -amylase and α -glucosidase can be monitored by colorimetric methods. A colorimetric assay based on the colour change of dinitrosalicylic acid has been used to screen various medicinal plants [170172], herbs and spices [121, 173]. The α -glucosidase inhibition assay uses p -nitrophenyl- α - d -glucopyranoside (PNPG) as the substrate.…”
Section: Screening Plants and Natural Products For Antidiabetic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Both the activity of α -amylase and α -glucosidase can be monitored by colorimetric methods. A colorimetric assay based on the colour change of dinitrosalicylic acid has been used to screen various medicinal plants [170172], herbs and spices [121, 173]. The α -glucosidase inhibition assay uses p -nitrophenyl- α - d -glucopyranoside (PNPG) as the substrate.…”
Section: Screening Plants and Natural Products For Antidiabetic Activitymentioning
confidence: 99%
“…Sixteen compounds including caffeic acid, luteolin glucoside, xanthomicrol, carvacrol, and luteolin were putatively identified from an Origanum glandulosum extract via LC–MS. Although the compounds were not evaluated individually, the extract showed dose-dependent α -amylase inhibitory potential similar to acarbose, and antioxidant activity comparable to trolox (an antioxidant analogue of vitamin E, used as a control in antioxidant assays) [170].…”
Section: Metabolite Profilingmentioning
confidence: 99%
“…Regarding Origanum glandulosum (syn. Origanum compactum ), Béjaoui et al [ 73 ] measured the antioxidant capacity of the methanolic extract, presenting an IC 50 value of 0.6 mg/mL for DPPH, attributed principally to the presence of caffeic acid, which has been reported as a potent antioxidant [ 74 ]. Another widely studied oregano species regarding antioxidant capacity is Origanum majorana , characterized by the high content of rosmarinic acid.…”
Section: Health Benefits Of Flavonoids and Phenolic Compounds Frommentioning
confidence: 99%
“…[32] The α-amylase inhibition property and antioxidant capacity of the major detected compounds such as caffeic acid, luteolin glucoside, xanthomicrol, and carvacrol from Origanum glandulosum were reported as a pharmacological effect. [33] In previous reports, researchers were reported that 3,.4,.5-trimethoxycinnamic acid as flavones showed antioxidant, anti-proliferative, antitumour, antimicrobial, oestrogenic, acetylcholinesterase, and anti-inflammatory activities, and was also used in treating cancer, cardiovascular disease, neurodegenerative disorders, etc., but we could not find any report on antidiabetic activity. [34] Phthalates (di(ethylhexyl) phthalate) are widely used as a plasticizer and are considered as a typical endocrine-disrupting chemical.…”
Section: Identification By Liquid Chromatography Mass Spectrometry (Lcms)mentioning
confidence: 99%